CIRSE Standards of Practice on Transjugular Intrahepatic Portosystemic Shunts - Lucatelli, Pierleone; Krajina, Antonín; Loffroy, Romaric; Miraglia, Roberto; Pieper, Claus Christian; Franchi-Abella, Stéphanie; Rocco, Bianca (Cardiovascular and interventional radiology, 2024)
BACKGROUND: Proposed in the early 1980s as a solution for managing complications of portal hypertension, the percutaneous creation of transjugular intrahepatic portosystemic shunt has consistently gained a central role. Increasingly lower complication rates have been observed thanks to improvements in both technologies and the skills of interventional radiologists. PURPOSE: This document is aimed at interventional radiologists and provides best practice recommendations for transjugular intrahepatic portosystemic shunt creation, describing patient selection, intraprocedural management and follow-up, in addition to recommendations in paediatric settings. METHODS: The CIRSE Standards of Practice Committee established a writing group consisting of seven European clinicians with recognised expertise in the creation of transjugular intrahepatic portosystemic shunt. The writing group reviewed the existing literature performing a pragmatic evidence search using PubMed to select relevant publications in the English language and involving human subjects, preferably published from 2009 to 2024. The final recommendations were developed by consensus. RESULTS: TIPS creation has an established role in the successful management of portal hypertension and its complications. This Standards of Practice document provides up-to-date recommendations for patient selection, materials, its safe performance, and follow-up with complications management.
Keywords: Hypertension, Portal; Portal hypertension; dítě; Portal hypertension-related ascites; Review Literature as Topic; Patient Selection; výběr pacientů; TIPS; transjugulární intrahepatální portosystémový zkrat; portální hypertenze; Portasystemic Shunt, Transjugular Intrahepatic; Variceal bleeding; přehledová literatura jako téma; PPG; Child; HVPG; Portosystemic shunt; lidé; Humans; Radiology, Interventional; intervenční radiologie